Assessing the impact of GBFS on mechanical behaviour and microstructure of soft clay. Issue 3 (16th March 2021) - Afrasiabian, Armin; Salimi, Mahdi; Movahedrad, Mehran; Vakili, Amir Hossein
ABSTRACT: In the present study, the kaolinite clay was mixed with different amounts of granulated blast furnace slag (GBFS) ranging from 0% to 30% by dry weight, and various experiments were performed such as pH, one-dimensional consolidation, unconfined compressive strength and scanning electron microscope (SEM). Stabilised specimens were placed in curing conditions at 20 and 45°C for 7, 28 and 90 days in order to investigate the interaction of soil and GBFS in normal and high temperatures. The results show that an increase in temperature leads to the faster growth of cementitious products such that the compressive strength of the samples containing 30% GBFS after 90 days of treatment at 20 and 45°C increased by as much as 2.33 and 9.33 times as compared to that of untreated soil, respectively. In addition, based on SEM images, the formation of more and faster cemented structures is confirmed by an increase in temperature.